Pengetahuan Dan Sikap Tentang Anemia Mempengaruhi Kepatuhan Minum Tablet Fe Pada Mahasiswi Prodi Keperawatan USN Kolaka - Afrianty, Iis; Naim, Rosani (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Anemia is a condition where there is a lack of red blood cells or what is commonly known as hemoglobin. Hemoglobin is needed to carry oxygen and if you have too few or abnormal red blood cells, or not enough, there will be a decrease in the blood's capacity to carry oxygen to the body's tissues. Teenage girls will menstruate every month so they are at higher risk of developing anemia due to iron deficiency. Observational Analytical research design with a Cross Sectional approach. The sample for this research was students from the Ninebelas November Kolaka University nursing study program. The technique used was simple random sampling, obtaining a sample of 86 respondents. The research instrument used was a questionnaire about knowledge and attitudes which had been tested for validity and reliability. The statistical test used is Chy Square. The research results showed that there was a significant relationship between knowledge and attitudes towards adherence to consuming blood supplement tablets